„Auf freiem Grund mit freiem Volke stehn“ — Zur prometheischen Freundschaft zwischen Hegel und Goethe: Dialethismus der Sittlichkeit - Kleemann, Ken Pierre (Revista Eletrônica Estudos Hegelianos, 2025)
The Faustian will has itself become an expression and an indictment of modernity. It accuses the Enlightenment of hybris of subjugating the world to knowledge. An image is created that both borrows questionably from the classical German heritage and rejects this tradition itself. Goethe, Hegel and ultimately, symbolically, Faust are stylized as figures of doom. However, through the friendship between Hegel and Goethe, the Enlightenment shows its true face. It is Promethean in the sense of Goethe’s design. Enlightenment as a project and undertaking is ultimately concerned with the project of critical metaphysics, not in order to become the master of the contradictions of the world, but to thematize the contradictory nature of the world itself. This Promethean friendship on the dialethism of morality shows a different model of enlightenment. It is not a dialectically overlapping image of modernity that remains, but rather the contradictoriness of the world itself that becomes the core of a laughing preoccupation of the citizen of this world.